EVALUASI DAMPAK SOSIAL DAN EKONOMI ALIH FUNGSI LAHAN HIJAU MENJADI KAWASAN INDUSTRI CANDI KOTA SEMARANG - Riko Avesiena Lazuardi Ahmad; Aufarul Marom; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Being green land transfer function to Candi Industrial Area is part of the development. In practice, these activities have impacts on the community and local government. The impact will be discussed here is the social and economic impacts of land transfer function being Candi Industrial Area. The purpose of the study is to identify the factors that affect the social and economic impacts of land use green to Temple Industrial Zone. Describes whether the economic and social impacts of land use green to Temple Industrial Area is in accordance with the desired impact. To evaluate the social and economic impacts of land use green to Temple Industrial Zone. And explain the improvement efforts that have been made. This study used seven socio-economic factors as well as six categories of evaluation such as effectiveness, efficiency, adequacy, equity, responsiveness and accuracy.